Herpes zoster, clinical course and associated diseases: A 5-year retrospective study at Ramathibodi Hospital - Sutasinee Tunsuriyawong (2018)
Objective: Herpes zoster was more frequently found in immunocompromised hosts and elderly persons than in general population. The aim of this study is to find out the distributions of skin lesions, treatments, complications of herpes zoster and associated diseases that occur in concomitant with or after herpes zoster infections. Material and Method: The medical records of the patients diagnosed as herpes zoster between January 1995 - December 2000 were reviewed. Only the patients who were followed up regularly at Ramathibodi hospital for at least 3 years after the first diagnosis of herpes zoster were enrolled into the study. Demographic data, distribution of skin lesions, treatments, complications of herpes zoster and associated diseases were recorded. Results: Three hundred and ninety-nine cases were enrolled in the study. Three hundred and ninety-eight patients (99.7%) had one dermatomal involvement. Sixty-seven patients (16.8%) had postherpetic neuralgia. Fifty-six patients had associated HIV infection. In 3 years followed up, 17 patients developed HIV infection, 3 patients developed acute leukemia, 2 patients developed mycosis fungoides.